Pengelolaan Pembelajaran IPA Berbasis Media Pembelajaran Science Education Quality Improvement Project (SEQIP)Kelas V SD Negeri Manahan Surakarta - Murwati, Tri; , Dr. Sofyan Anif, M.Si; , Dr. Djalal Fuadi, M.M (2017)
The purpose of this study was to describe (1) the learning plan Science-Based Media Learning Science Education Quality Improvement Project (SEQIP) in class V SD Negeri Manahan; (2) the implementation of IPA-based learning Media Education Science Education Quality Improvement Project (SEQIP) in class V SD Negeri Manahan; and (3) assessment of learning Science-Based Media Learning Science Education Quality Improvement Project (SEQIP) in class V SD Negeri Manahan. The research is a qualitative research with ethnographic research design. The research location is on SD Negeri Surakarta Manahan. Mechanical pengumplan data using in-depth interviews, documentation, and observation. Analysis of the data using three stages: data reduction, data presentation, and drawing conclusions with verification. The results of this study show that planning SEQIP based Learning science in class V SD Negeri Manahan Surakarta, made by teachers in the form of lesson plan (RPP), as a routine activity compiled at the beginning of the new school year. Before developed by teachers, lesson plan created by the group. To plan the implementation of IPA-based media pembelaran SEQIP, teachers reviewing syllabuses, elaborated in the form of indicators, compiling teaching materials, making learning steps, determine the allocation of time, develop assessment, determine remedial learning, and determine media and learning resources. Implementation of science teaching based Learning Media Science Education Quality Improvement Project (SEQIP) in class V SD Negeri Manahan is a form of implementation of the lesson plan that had been developed by teachers, which was preceded by the activities of teachers to prepare tools and materials composed of a tool kit pupil, tools of the teacher kit and an instruction manual KIT IPA. The learning process using instructional media KIT IPA with the method of demonstration and practice. Assessment of learning science Learning Media Based Science Education Quality Improvement Project (SEQIP) conducted by teachers to measure how far the knowledge, skills and attitudes that have been achieved by students. In addition to completing the learning process, the assessment is also giving feedback to teachers, students, schools and parents. Keywords: planning, implementation, assessment, SEQIP, IPA